Harmonic distortion due to output conductance in SI cells - Abuelma’atti, M.T. (1998)
This comment relates to a recently published letter (see J. Martins and V. Dias, ibid., vol.33, pp.127-8, 1997) in which a closed-form expression for the effect of the output conductance on harmonic distortion in the second-generation switched-current (SI) memory cell is presented